2010
DOI: 10.1016/j.marpolbul.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal extension of eutrophication associated with shrimp farm wastewater discharges in the New Caledonia lagoon

Abstract: Shrimp farming in New Caledonia typically uses a flow-through system with water exchange rates as a tool to maintain optimum hydrological and biological parameters for the crop. Moreover, the effluent shows hydrobiological characteristics (minerals, phytoplankton biomass and organic matter) significantly higher than that of the receiving environment. Separate surveys were carried out in a bay (CH Bay) with a medium-size intensive farm (30 ha) (PO) and in a mangrove-lined creek (TE Creek) near a larger semi-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 41 publications
6
37
1
2
Order By: Relevance
“…Nonetheless, the high chl-a concentration rapidly decreased along the Selang Sibu River down to 0.919 ± 0.379 mg m -3 at the conjunction with Sibu Laut River. The observation was in good agreement with the study of Thomas et al (2010) and Trott and Alongi (2000). The decrease of the chl-a may be due to the dilution or high grazing rate of zooplankton on phytoplankton as suggested by La Rosa et al (2002).…”
Section: General Environmental Variablessupporting
confidence: 89%
See 1 more Smart Citation
“…Nonetheless, the high chl-a concentration rapidly decreased along the Selang Sibu River down to 0.919 ± 0.379 mg m -3 at the conjunction with Sibu Laut River. The observation was in good agreement with the study of Thomas et al (2010) and Trott and Alongi (2000). The decrease of the chl-a may be due to the dilution or high grazing rate of zooplankton on phytoplankton as suggested by La Rosa et al (2002).…”
Section: General Environmental Variablessupporting
confidence: 89%
“…Tidal mangrove estuaries have some capacity to process the intermittent inputs of pond-derived nutrients at least over short spatial and temporal scales. Thomas et al (2010) and Ribeiro and Kjerfve (2002) also reported similar water quality improvement with distance. The dilution factor along Selang Sibu River was varied among phosphorus species.…”
Section: General Environmental Variablesmentioning
confidence: 55%
“…The immobilized microalgae have been exploited for removing nutrient in wastewater [2,3] and have great potential to be used in marine aquaculture wastewater treatment. Effluents from aquaculture are rich in solids and dissolved nutrients, mainly in the form of inorganic nitrogen and phosphorus [4,5]. Effluents from aquaculture industry should be treated before discharge into its adjacent aquatic ecosystem to avoid eutrophication and water contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian water quality standards for TAN and total phosphorus are ≤0.4 mg·L −1 and ≤0.12 mg·L , respectively. Various studies with monitoring of effluent and influent water quality in shrimp farms report similar results [29,38,[60][61][62][63][64]. Additionally, several researches have demonstrated effluent water from shrimp ponds typically contains elevated concentrations of dissolved nutrients compared to influent water [29,61,62,64].…”
Section: Assessment Of Water Qualitymentioning
confidence: 72%